Fire design of wood connections loaded in shear - Fonseca, Elza M M (2019)
The main objective of this work is to compare the fire resistance between wood-steel-wood (W-S-W) and wood-wood-wood (W-W-W) connections, both joined by steel dowel fasteners, in double shear. The analytical and design procedures follow simplified equations presented in Eurocode 5, part 1-1 and 1-2. A computational methodology, based on finite element method, was also implemented to produce two dimensional thermal simulations, which permits to verify the heating effect through the dowels fasteners or steel elements through the connection in study. Different cross-sections will be identified, considered as the most relevant parts, to compare the temperature distribution in the studied connections. According to the fire exposure, a thermal and transient effect will happen and a char-layer appearing in the exposure side of the connections. The measured quantity of the charred area permits to identify the lost structural material in the studied cross-sections. The charring rate will calculate and compared with the constant value proposed by the Eurocode 5, part 1-2. There are typical values for the charring rate of wood between 0.5-1.0mm/min according to Eurocode 5, part 1-2. However, as a general conclusion and additional information to help designers and professionals, the number of fasteners increases with the applied load, lower dowels diameters have higher effect in the number of fasteners, at fire exposure the steel fasteners bring the heat to inside the connections, and different wood densities affect the thermal behaviour and the charring rate evolution. The charring rate permits to quantify the lost layer thickness and the fire resistance of the connection, dependent on the chosen material density.